Confocal laser scanning microscopy (CLSM) as a new tool for morphological characterisation of both newly collected and museum voucher specimens of the Trypanorhyncha Diesing, 1863 (Platyhelminthes: Cestoda) - Neitemeier-Duventester, Xaver; Bick, Andreas; Theisen, Stefan; Palm, Harry W (Folia parasitologica, 2022)
Taxonomic issues within Trypanorhyncha, e.g., the inaccurate light microscopic visualisation of the hook patterns, are solvable by confocal laser scanning microscopy (CLSM). We applied CLSM imaging to study Trygonicola macropora (Shipley et Hornell, 1906) and Dollfusiella michiae (Southwell, 1929) from Neotrygon caeruliopunctata Last, White et Séret from Bali, Indonesia. To illustrate the strength and limitations of CLSM, images of Otobothrium cysticum (Mayer, 1842) and Symbothriorhynchus tigaminacantha Palm, 2004, both permanent mounts from a collection, were also processed. The CLSM created image stacks of many layers, and edited with IMARIS Software, these layers resulted in three-dimensional images of the armature patterns and internal organs of both species. BABB (benzylalcohol and benzylbenzuolate) clearing was applied to T. macropora. We conclude that trypanorhynch cestodes stained with Mayer-Schuberg's acetic carmine permanently mounted in Canada balsam are suitable for CLSM, allowing detailed analyses of museum type-material as well as freshly collected and processed worms. BABB resulted in imaging the testes in detail, suggesting other stains to be used for CLSM in trypanorhynch cestode research. Application of CLSM for studies of other cestode groups is highly recommended.
Keywords: Animals; ploštěnci; Otobothrium cysticum; Cestoda; taxonomy; Skates, Fish; Museums; muzea; Trygonicola macropora; Symbothriorhynchus tigaminacantha; Mayer-Schuberg's acetic carmine; rejnokovití; fish parasites; Dollfusiella michiae; benzyl alcohol/benzyl benzoate (BABB) clearing; Neotrygon caeruleopunctata; Platyhelminths; zvířata; Microscopy, Confocal; konfokální mikroskopie; Indonesia